2013
DOI: 10.3109/09273948.2012.752013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Chronic Uveitis following Cataract Surgery

Abstract: Postsurgical uveitis developed after approximately 1 in 400 cataract surgeries and occurred more frequently in eyes experiencing intraoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…The incidence of persistent iritis in our study was 0.32%, which is similar to that previously reported by Patel et al [3]. The incidence was 0.24% in Patel’s study with the exclusion criteria similar to those of our own study: duration of iritis less than 6 months, prior uveitis or underlying systemic disease, penetrating trauma, endophthalmitis, retained lens material, neovascular glaucoma, and prior intraocular surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence of persistent iritis in our study was 0.32%, which is similar to that previously reported by Patel et al [3]. The incidence was 0.24% in Patel’s study with the exclusion criteria similar to those of our own study: duration of iritis less than 6 months, prior uveitis or underlying systemic disease, penetrating trauma, endophthalmitis, retained lens material, neovascular glaucoma, and prior intraocular surgery.…”
Section: Discussionsupporting
confidence: 90%
“…A study performed at Vanderbilt University found a significant association between postsurgical uveitis and intra-operative complications, as well as worse visual acuity outcomes. The median duration of inflammation was 10 months [3]. In a review of rheumatoid arthritis patients undergoing cataract surgery, elevated pre-operative rheumatoid factor (RF) serum titers were associated with 1+ aqueous cell 1 month after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Hypopion was noted in one of our cases, this clinical feature was reported by several authors in approximately 46% of the cases of CPE (8, [11][12][13][14]. A white plaque on the anterior surface of the IOL or on the posterior capsule, was noted in all our patients, this nding was reported in 28.5% to 100% of CPE (11,14,15) and was found to be mostly associated with P.acnes (12,(16)(17)(18)(19)(20). Others clinical features were noted in literature, suggesting fungal infection, such as a stirringly white in ltrates or clumps in the anterior chamber (16,21,22).…”
Section: Discussionsupporting
confidence: 61%
“…The first point is to always consider the intraocular lens position in patients with persistent anterior segment inflammation following cataract surgery. Chronic post-operative uveitis (persistent inflammation more than 6 months after cataract surgery) has been quoted as occurring in 1 in 400 operations with a much higher incidence in those eyes that had an intraoperative complication [ 6 ]. In our case the important signs of endothelial pigment deposition and inferior iris transillumination defects made us very suspicious that the intraocular lens may have been in the sulcus rather than in the capsular bag, and was therefore leading to iris chaffe and pigment shedding causing the persistent inflammation and high intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%